Meningkatkan Kemampuan Membaca Awal Dengan Model SIUUL (Simak-Ucap-Ulang) Pada Anak Usia Dini Kelompok A Di RA Jami’atu Ta’limil Qur’an - Nurlatifah, Intan; Watini, Sri; Yuntina, Lily (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Reading skill in children is a skill that everyone really wants to have, introducing reading to children is good because the brain of young children is in its golden age, good stimulation will make the child’s brain able to absorb all learning well. This research aims to improve the early reading skills of young children using the SIUUL (listen-speak-repeat) model at RA Jami’atu Ta’limil Qur’an. This is because the level of children’s reading ability is relatively low. Classroom action research (PTK) uses the kemmis & Mc Taggart method. The subjects of this research were group A students with a total of 14 students consisting of 7 boys and 7 girls. The conclusions in this research are divided into pre-cycle, cycle I and cycle II. In the pre-categorized 48,85%, cycle I 56,94%, cycle II 80,89%